Serum immunoglobulins and white blood cells in Polish athletes from different sport disciplines - Witek, K.; Orysiak, J.; Sitkowski, D.; Lerczak, K.; Malczewska Lenczowska, J.; Grochowska, J.; Pintera, M.; Hubner-Wozniak, E.; Pokrywka, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Immunoglobulins (Ig) and white blood cells (WBC) are very important elements in the immune system, playing a role in defense against disease agents. Regular physical exercise influences the number of immune markers. However, these changes depend on the type of physical exercise (Saygin et al. 2006, Orysiak et al. 2012). The aim of this study was to compare the levels of serum immunoglobulins (IgA, IgM, IgG), white blood cell counts and their subsets (neutrophiles, lymphocytes and monocytes) in ice hockey players, volleyball players and rowers. Methods: The samples were collected from 125 male polish athletes (aged 18,2±3,1 years) that were representing three different sport disciplines: ice hockey, rowing and volleyball. Blood samples were taken after night fasting from healthy, medically examined athletes. The haematology parameters were measured using haematology analyzer ADVIA 120 (Siemens, Germany). Immunoglobulin concentrations were measured using turbidimetric methods by means of biochemical analyzer PENTRA 400 (Horiba, France). Results: The lowest concentrations of IgA, IgG and IgM were found in ice hockey players (1,42 ± 0,59 g/l, 8,85 ±2,06 g/l, 0,81±0,29 g/l, respectively). The lowest WBC, neutrophil and lymphocyte counts were noted in rowers (5,83±1,50 x103/ul, 3,02±1,41 x103/ul, 1,97±0,46 x103/ul, respectively). In this study, only IgG concentration was significantly different among sport disciplines. Significant changes in IgG concentration occurred in ice hockey players compared with rowers and volleyball players (8,85±2,06 x103/ul, 10,87±2,65 x103/ul, 13,60±2,32 x103/ul, respectively; p<0,05) and in rowers compared with volleyball players (p<0,05). Conclusion: The observed differences in IgG levels depend on the sport disciplines and could be related to the adaptive response to the physical exercise.